National identity in the context of globalization - Turgumbayeva К.М. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2022)
Today, the category of identity acts as a kind of prism through which the key components of the formation of a community are rethought. In a broad sense, the categories of «nation» and «national identity» are closely intertwined. In the history of the development of society, the emergence of a nation is inseparable from the emergence of a national state and a territorial community. The state itself is formed around the nation as a political community, therefore such states of the modern type are called the «nation-state». The relationship between the nation and the state gives a special specific significance to national identity among other social constructs. The modern development of society is characterized by a high degree of intensification of globalization processes in all spheres of social development. Touching on the fundamental principles of the concepts of community and personality, the globalization process dictates the need to rethink some of the traditional ideas. This article deals with the problem of preserving national identity, which modern society faces in the context of the globalization process. The author considers the main theoretical approaches to the study of globalization. This analysis is necessary to identify existing problematic aspects. As a result, a number of factors affecting the transformation of national identity were identified. The influence of globalization as the main factor influencing the modernization of national identity as a social construct as a whole is considered. The role of the national identity of Kazakhstan in the context of ensuring national security is determined. Globalization processes have a significant impact on the national identity of Kazakhstan, which determines the need for modernization and transformation of this social construct. Understanding traditional approaches in the context of global changes will allow us to find our own way of building an effective state policy in the field of national identity.